Cost of illness due to respiratory syncytial virus acute lower respiratory tract infection among infants hospitalized in Argentina - Julia Dvorkin; Emiliano Sosa; Elizabeth Vodicka; Ranju Baral; Andrea Sancilio; Karina Dueñas; Andrea Rodriguez; Carlos Rojas-Roque; Patricia B. Carruitero; Fernando P. Polack; Clint Pecenka; Romina Libster; et al. (BMC Public Health, 2024)
Abstract Background Information is scarce regarding the economic burden of respiratory syncytial virus (RSV) disease in low-resource settings. This study aimed to estimate the cost per episode of hospital admissions due to RSV severe disease in Argentina. Methods This is a prospective cohort study that collected information regarding 256 infants under 12 months of age with acute lower respiratory tract infection (ALRTI) due to RSV in two public hospitals of Buenos Aires between 2014 and 2016. Information on healthcare resource use was collected from the patient’s report and its associated costs were estimated based on the financial database and account records of the hospitals. We estimated the total cost per hospitalization due to RSV using the health system perspective. The costs were estimated in US dollars as of December 2022 (1 US dollar = 170 Argentine pesos). Results The mean costs per RSV hospitalization in infants was US$587.79 (95% confidence interval [CI] $535.24 – $640.33). The mean costs associated with pediatric intensive care unit (PICU) admission more than doubled from those at regular pediatric wards ($1,556.81 [95% CI $512.21 – $2,601.40] versus $556.53 [95% CI $514.59 – $598.48]). Conclusions This study shows the direct economic impact of acute severe RSV infection on the public health system in Argentina. The estimates obtained from this study could be used to inform cost-effectiveness analyses of new preventive RSV interventions being developed.